Tillid i kreative samarbejder - Redvall, Eva Novrup; Strandvad, Sara Malou (Peripeti, 2011)
Trust in Creative Collaborations. This article considers trust as a central ingredient in creative collaboration. Based on several case studies of development processes in the Danish film industry, the analysis exemplifies three kinds of trust: 1) calculative trust in emerging collaborations, 2) trust based on relations or identity in established collaborations, and 3) knowledge-based trust in the institutional field.